Antibody structure and engineering considerations for the design and function of Antibody Drug Conjugates (ADCs). (4th March 2018) - Hoffmann, Ricarda M.; Coumbe, Ben G. T.; Josephs, Debra H.; Mele, Silvia; Ilieva, Kristina M.; Cheung, Anthony; Tutt, Andrew N.; Spicer, James F.; Thurston, David E.; Crescioli, Silvia; Karagiannis, Sophia N.
ABSTRACT: Antibody-drug conjugates (ADCs) are emerging as effective tools in cancer therapy, combining the antibody's exquisite specificity for the target antigen-expressing cancer cell together with the cytotoxic potency of the payload. Much success stems from the rational design of "toxic warheads", chemically linked to antibodies, and from fine-tuning the intricate properties of chemical linkers. Here, we focus on the antibody moiety of ADCs, dissecting the impact of Fab, linkers, isotype and Fc structure on the anti-tumoral and immune-activating functions of ADCs. Novel design approaches informed by antibody structural attributes present opportunities that may contribute to the success of next generation ADCs.